2014
DOI: 10.1007/s13278-014-0237-x
|View full text |Cite
|
Sign up to set email alerts
|

Clustering memes in social media streams

Abstract: The problem of clustering content in social media has pervasive applications, including the identification of discussion topics, event detection, and content recommendation. Here we describe a streaming framework for online detection and clustering of memes in social media, specifically Twitter. A pre-clustering procedure, namely protomeme detection, first isolates atomic tokens of information carried by the tweets. Protomemes are thereafter aggregated, based on multiple similarity measures, to obtain memes as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…The authors also find that exogenous factors are more important than epidemic spreading in establishing hashtag popularity. JafariAsbagh et al () propose a streaming framework for detecting and clustering memes in online social networks. Bao et al (2013) investigate the cumulative effect of information diffusion on Weibo and argue that additional exposures do not improve the probability of retweets.…”
Section: Introductionmentioning
confidence: 99%
“…The authors also find that exogenous factors are more important than epidemic spreading in establishing hashtag popularity. JafariAsbagh et al () propose a streaming framework for detecting and clustering memes in online social networks. Bao et al (2013) investigate the cumulative effect of information diffusion on Weibo and argue that additional exposures do not improve the probability of retweets.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we have shown that it possible to provide a guide that leads to the creation of effective models, and this does provide some systematic structure to the creation of thematic models. However, more work is needed to explore whether models could be constructed in an automatic way, for example by using clustering techniques to derive coherent terms and concepts from social media streams [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Twitter allows users to utilize the "#" symbol, called hashtag, to mark keywords or topics in a Tweet; an image is usually associated with multiple labels which are characterized by different regions in the image; users are able to build connection with others (link information). Previous text analytics sources most often appear as <user, content> structure, while the text analytics in social media is able to derive data from various aspects, which include user, content, link, tag, timestamps and others [62,63,64].…”
Section: Challengesmentioning
confidence: 99%